2015
DOI: 10.1212/wnl.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease

Abstract: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…An international, multicenter candidate gene study 16 evaluated the role of common mutations in these genes in nonlobar ICH, small vessel ischemic stroke and magnetic resonance imaging-defined white matter hyperintensities. An intronic locus within COL4A2 was strongly associated specifically with risk of nonlobar ICH, with rs9521733, the top associated SNP within this locus, resulting in a 29% increase in risk of this type of brain bleed.…”
Section: Col4a1 and Col4a2: An Example Of Rare And Common Genetic Conmentioning
confidence: 99%
“…An international, multicenter candidate gene study 16 evaluated the role of common mutations in these genes in nonlobar ICH, small vessel ischemic stroke and magnetic resonance imaging-defined white matter hyperintensities. An intronic locus within COL4A2 was strongly associated specifically with risk of nonlobar ICH, with rs9521733, the top associated SNP within this locus, resulting in a 29% increase in risk of this type of brain bleed.…”
Section: Col4a1 and Col4a2: An Example Of Rare And Common Genetic Conmentioning
confidence: 99%
“…For lacunar stroke, several genetic loci have been identified for sporadic lacunar stroke and singlegene disorders causing cerebral small vessel diseases. 113,114 With these results, there have been efforts to generate a genetic risk score for ischemic stroke, but further studies are needed because the improvement in clinical risk prediction with genetic models was found to be small.…”
Section: Research Needs and Gapsmentioning
confidence: 99%
“…Furthermore, it has been suggested that shared molecular mechanisms could underlie both monogenic and sporadic SVD, and some support for this hypothesis is emerging from studies looking at associations between common polymorphism in genes causing monogenic SVD and sporadic SVD. Common variants in COL4A1/A2 were associated with a spectrum of SVD phenotypes including lacunar stroke, WMH and subcortical ICH [56]. Common Notch3 polymorphisms were associated with an increased risk of age-and hypertension-related white matter lesions [57], although this finding could not be replicated in younger onset lacunar stroke [5].…”
Section: What Can We Learn From Monogenic Svd About Disease Mechanisms?mentioning
confidence: 99%
“…Increased blood brain barrier (BBB) permeability is associated with increasing age, and is thought to be a contributing factor to sporadic small vessel disease [62]. The mechanism of stroke in COL4A1 and COL4A2-related arteriopathy, combined with the finding that more common variants in COL4A1 are associated with sporadic SVD [56], thus providing further evidence for the role of BBB compromise, whether due to genetics or ageing, in sporadic SVD.…”
Section: Loss Of Vessel Wall Integritymentioning
confidence: 99%